(untitled) (CIPEEX, 2025)
The objective of the study project is to compare the functional effects of ten sessions of neurofunctional training associated with repetitive transcranial magnetic stimulation (rTMS) on the active and placebo dorsolateral prefrontal cortex in children with ASD. This is a randomized, placebo-controlled, double-blind clinical trial involving 24 children diagnosed with ASD, aged between three and eight years. The children will be randomly allocated into two groups: Experimental group - neurofunctional training and active rTMS, and Control group - neurofunctional training and placebo rTMS. The participants will be evaluated one week before the intervention, one week and one month after the end of the interventions, using the Childhood Autism Rating Scale, the Autism Classification System: Social Communication, timed up and go, the 10-meter walk test, the Pediatric Balance Scale, and the Participation and Environment Measure for Children and Youth. The interventions will be held five times a week, carried out over two consecutive weeks. rTMS will be applied to the left dorsolateral prefrontal cortex for 20 minutes, at a high frequency (5Hz). After the application of rTMS, the participants will undergo neurofunctional training for 20 minutes. The neurofunctional training will consist of an activity circuit (10 minutes) and treadmill gait training (10 minutes). The results will be statistically analyzed assuming a significance level of p≤0.05.